Analisis Pengaruh Kinerja Ekonomi, Pengungkapan Kinerja Sosial dan Lingkungan Terhadap Nilai Perusahaan - Benita Nur Fajriyah; Hotman Tohir Pohan (Publikasi Indonesia, 2022)
This research aims to examine the effect of economic performance, disclosure of social and environmental performance on firm value with leverage and firm size as control variable. The population used in this research are mining companies listed on the Indonesia Stock Exchange (IDX) in 2018-2021 with total sample of 36 samples obtained from the purposive sampling method. The type of data from this research is secondary data that derived from company’s annual reports and sustainability reports. The researcher conducted the test through descriptive statistical tests, multiple regression analysis, classical assumption tests, and research hypothesis testing. The results of this research is indicate that economic performance, disclosure of social performance, and disclosure of environmental performance have a positive effect on firm value.